(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2023)
We propose a symbolic investigation of two publications posted on Instagram by Heineken and Carrefour. This choice was made because they represent the idea of “political correctness”. The objective is to analyze these communications from an imaginary theories perspective, as suggested by M. Contrera, G. Durand, C. Jung, and others, as this action allows the identification of hidden aspects in the publications and the perception of what information is there, however, in addition to the obviousness of commercial interests that aim to reinforce the brand’s good public reputation. Our conclusions suggest that it is possible to change this biased perception by building a critical mass sufficiently qualified to recognize these mechanisms that lead to communication one-sidedness.